Effects of CYP3A4 and P-glycoprotein inhibition or induction on the pharmacokinetics of ubrogepant in healthy adults: Two phase 1, open-label, fixed-sequence, single-center, crossover trials. (5th August 2021) - Jakate, Abhijeet; Boinpally, Ramesh; Butler, Matthew; Ankrom, Wendy; Dockendorf, Marissa F; Periclou, Antonia
Background: Ubrogepant is metabolized by cytochrome P450 3A4 (CYP3A4) and is a P-glycoprotein (P-gp) substrate. Objective: To assess effects of multiple-dose moderate-strong CYP3A4 and strong P-gp inhibitors and inducers on ubrogepant pharmacokinetic (PK) parameters. Methods: Two phase 1, open-label, fixed-sequence, single-center, crossover trials enrolled healthy adults to receive ubrogepant 20 mg with/without verapamil 240 mg (a moderate CYP3A4 inhibitor) or ketoconazole 400 mg (a strong CYP3A4 and P-gp transporter inhibitor) (Study A), or ubrogepant 100 mg with/without rifampin 600 mg (a strong CYP3A4 inducer and P-gp inducer) (Study B). Outcomes included ubrogepant PK parameters (area under plasma concentration-time curve, time 0 through infinity [AUC0-∞ ], peak plasma concentration [Cmax ]), and safety (treatment-emergent adverse events [TEAEs]). PK parameters were compared between ubrogepant with/without coadministered medications using linear mixed-effects models. Cmax and AUC0-∞ least-squares geometric mean ratios (GMR) of ubrogepant with/without coadministration were constructed. Results: Twelve participants enrolled in Study A and 30 in Study B. AUC0-∞ and Cmax GMR (90% CI) were 3.53 (3.32–3.75) and 2.80 (2.48–3.15), respectively, for ubrogepant with verapamil; 9.65 (7.27–12.81) and 5.32 (4.19–6.76) with ketoconazole; and 0.22 (0.20–0.24) and 0.31 (0.27–0.36) with rifampin. TEAEs were predominantly mild; no treatment-related serious TEAEs or TEAE-related discontinuations occurred. Conclusion: The PK of ubrogepant were significantly affected by the concomitant use of CYP3A4 moderate-strong inhibitors and strong inducers.